(w + x)(w + x)

Question

Asked 12/22/2014 7:31:06 AM

Updated 12/22/2014 7:48:20 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [12/22/2014 7:47:10 AM]

debnjerry|Points 65785|

debnjerry|Points 65785|

Question

Asked 12/22/2014 7:31:06 AM

Updated 12/22/2014 7:48:20 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [12/22/2014 7:47:10 AM]

Rating

3

(w + x)(w + x)

= w^2 + wx + wx + x^2;

= w^2 +2wx + x^2

= w^2 + wx + wx + x^2;

= w^2 +2wx + x^2

Added 12/22/2014 7:48:20 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/22/2014 2:32:21 PM]

(y - x)(y - x) **Weegy:** (y - x)(y - x) = y^2 - xy - xy + x^2 = y^2 - 2xy + x^2 (More)

Question

Expert Answered

Updated 12/22/2014 1:09:58 PM

0 Answers/Comments

a2 - 5a - 6 **Weegy:** (5a - 7)(2a - 1) = 10a^2 - 5a - 14a + 7; = 10a^2 - 19a + 9; The middle term is: -19a (More)

Question

Updated 12/22/2014 9:55:48 AM

1 Answer/Comment

a2 - 5a - 6 = (a + 1)(a - 6)

Added 12/22/2014 9:55:47 AM

This answer has been confirmed as correct and helpful.

(2x + 4)(3x + 8 ) **Weegy:** 3x + 1 = 2x + 3 3x - 2x = 3 - 1 x = 2 (More)

Question

Updated 12/23/2014 12:16:44 AM

1 Answer/Comment

29,299,940

questions answered

There are no comments.